SISTEM MANAJEMEN KEAMANAN INFORMASI MENGGUNAKAN ISO 27001 PADA SISTEM INFORMASI PENELUSURAN PERKARA (SIPP) - Dida, Gilang Derman; Snae, Menhya (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine whether there is an influence of foreign tax credits on the effective tax burden of corporate taxpayers in Indonesia. Foreign tax credits have a major influence on the effective tax burden of corporate taxpayers in Indonesia. The existence of this mechanism will allow companies to avoid double taxation, optimize tax payments, and can also reduce the effective tax rate, this can increase the probability and compliance of tax payments. This study uses a qualitative descriptive method that focuses on explaining and analyzing phenomena based on non-numerical data. Much of the data in this study was obtained through the library research method, namely by collecting, reviewing, and examining many sources of literature related to the research theme. The sources of literature used include academic books, scientific journals, relevant articles, and other official documents that support the understanding of the concepts and implementations studied. the results of this discussion support the hypothesis that KPLN (foreign tax credits) have an effect on reducing ETR (effective tax burden), and show the importance of careful international tax management to maximize tax efficiency legally.